2019
DOI: 10.5171/2019.463316
|View full text |Cite
|
Sign up to set email alerts
|

How Social Inclusion Promotes Sales: An Analysis of the Example of Employing People with Disabilities

Abstract: Although social inclusion is an important aspect of corporate social responsibility (CSR), it has received little attention in the literature and research on the subject. However, it is increasingly recognized that more attention needs to be paid to this area: When making purchasing decisions, customers are increasingly looking for companies that act (and credibly demonstrate) in a sustainable and socially responsible manner. Customers are more aware of product-related CSR activities than philanthropy or susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
3
0
4
Order By: Relevance
“…Although sales growth is significantly lower in 2019 than in 2018, it is crucial to highlight that sales per employee did not fall by the same proportion, which shows an improvement in the efficiency of human resources. This is in line with previous studies [64]. The financial risk is relatively low in the period, mainly in the later years.…”
Section: Descriptivessupporting
confidence: 93%
See 1 more Smart Citation
“…Although sales growth is significantly lower in 2019 than in 2018, it is crucial to highlight that sales per employee did not fall by the same proportion, which shows an improvement in the efficiency of human resources. This is in line with previous studies [64]. The financial risk is relatively low in the period, mainly in the later years.…”
Section: Descriptivessupporting
confidence: 93%
“…Bearing in mind the main characteristics of sheltered employment centres, the business sector variable was divided into two parts: service and manufacturing companies, since previous studies have shown that most of these centres operate in the service sector. We chose the variable sales growth because research carried out by Miethlich and Oldenburg [64] has shown that social inclusion, as part of the Corporate Social Responsibility strategy, contributes in a positive way to sales growth. In addition to these ratios, the fundamental economic and financial ratios necessary for the company's profitability were analysed [62].…”
Section: Data Collection Variables and Methodologymentioning
confidence: 99%
“…The turn to the economy took place, although gradually, but rather dynamically and wavily. The similar result was shown by other authors' studies (Krutzinna & Floridi, 2018;Miethlich & Oldenburg, 2019;Sánchez et al, 2016;Zhuravleva & Chernonozhkina, 2018). This process was influenced by world changes in socio-cultural, legal, religious, economic spheres.…”
Section: Introductionsupporting
confidence: 90%
“…Svarbu formuoti teigiamą visuomenės požiūrį į asmenis, turinčius psichosocialinę negalią. Užsienio šalių patirtis atskleidė, kad daugėja socialiai atsakingų įmonių, kurios įdarbina asmenis, turinčius negalią, ir taip prisideda prie socialinės įtraukties plėtros darbo rinkoje, tai netgi tampa organizacijų strateginio planavimo dalimi (Miethlich, Oldenburg, 2019). Kita vertus, kalbėjimas apie teisę į darbą skamba beprasmiškai, jeigu darbo vieta nepritaikyta asmeniui, turinčiam negalią, pvz., kurtieji ar neprigirdintieji, aklieji, žmonės, kurių silpnas regėjimas, ar turintieji kognityvinių funkcijų sutrikimą negali naudotis darbo vietoje įdiegtomis technologijomis (Blanck, 2020).…”
Section: Socialinės įTraukties Problemos Kylančios Asmenims Turintiems Psichosocialinę Negaliąunclassified